Validation of Yonsei-Bilateral Activity Test (Y-BAT)-Bilateral Upper Extremity Inventory Using Rasch Analysis. (October 2020) - Lee, Joo-Hyun; Hong, Ickpyo; Park, Ji-Hyuk; Shin, Joon-Ho
There is little assessment to provide specific information about quality of bilateral upper extremity movement specifically. This study examined the psychometric properties of the Yonsei-Bilateral Activity Test (Y-BAT). An observational cross-sectional design was used with 100 stroke survivors. Unidimensionality was examined using factor analyses, and Rasch analysis was used to test rating scale structure, fit statistics, and precision of the Y-BAT. The Y-BAT demonstrated a unidimensional measurement construct, and 19 of the 27 items fit the Rasch model. The instrument demonstrated good precision, including person reliability and person strata. The Y-BAT estimated person measures within a wide range of theta values with a reliability of .9 with good precision. Our results indicate that a revised, 19-item version of the Y-BAT demonstrates sound internal validity and may be a useful instrument for clinicians to measure upper extremity function with good precision following stroke.